TINGKAT SELF EFFICACY MAHASISWA PRODI BIMBINGAN DAN KONSELING IKIP PGRI PONTIANAK - Sukmawati, Ema; Hidayati, Novi Wahyu (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to describe student self-efficacy by providing an understanding of several problems related to students' lack of learning and lack of confidence in their abilities. The research used in this research is a quantitative approach. The quantitative approach emphasizes the analysis of numerical data (numbers) which are processed using statistical methods. The respondents in this research were 43 third semester students of the Guidance and Counseling Study Program at IKIP PGRI Pontianak. Based on the research results, it can be seen that the relationship between self-efficacy and students' anxiety levels. Students who have self-efficacy were obtained from 43 respondents, 13 students had low self-efficacy and were not anxious (30.23%), 12 students were mildly anxious (27.90). %), moderately anxious as many as 9 students (20.93), severely anxious 7 students (16.27%), panicked 2 students (4.6%), This shows that there is a relationship between self-efficacy and the level of anxiety in guidance and counseling study program students in the third semester From the results of the research above, the researcher assumes that the relationship between self-efficacy and anxiety levels is sufficient to influence students in the guidance study program and, therefore, it can be concluded that there is a relationship between self-efficacy and students' anxiety levels. students are in the moderate anxiety category. There is a p-value = 0.000 < significance value α = 0.05 and r = -0.506, which means there is a significant relationship in the negative direction between self-efficacy and student anxiety with a moderate level of correlation.